EFFICACY OF PERTURBATION TRAINING IN IMPROVING BALANCE AND FUNCTION IN THE MANAGEMENT OF KNEE OSTEOARTHRITIS - Bhaskar, Brillya; T U, Jimshad; Solomen, Subin (International journal of physiotherapy, 2019)
Background: Subjects who are suffering from osteoarthritis of the knee will have problems including progressive loss of function, depending on walking, climbing stairs, and it may affect lower extremity functions. Balance is a major component required for the activities of daily living and functions. The objective of the study was to compare the effectiveness of perturbation training and conventional physiotherapy in improving balance and function in the rehabilitation of knee osteoarthritis. Method: Study design was an experimental study. Thirty subjects (16 males and 14 females) suffering from knee osteoarthritis were randomized into a control group and experimental group. Fifteen subjects in the control group were treated with traditional methods like ultrasound, stretching and strengthening, and fifteen subjects in the experimental group were given perturbation training along with the conventional method. Outcome measures used were Timed get up and go test score (TUG) and Functional reach test score (FRT) scales, pre-assessed on Day 1. Each group received 14 sessions of treatment, after which post-assessment of outcome measures was done. Results: Timed get up and go test score was reduced in both groups after training, which was statistically significant (p<.05). The functional reach test score was increased after training in both groups, which was statistically significant (p<.05). However, comparing between groups, the experimental group showed more reduction in TUG score and improvement in the FRT score, which was statistically significant (p<.05). Conclusion: Perturbation training given with conventional treatment was found to have a significantly better effect in improving the function of the lower extremity in OA knee subjects. However, a well-designed trial, including a larger sample size with repeated measurements, is needed to find out the effectiveness of training with perturbation in the management of knee osteoarthritis and generalize it in a larger population.